Stroke as the First Clinical Manifestation of Takayasu's Arteritis - Caldeira Pereira, Vanessa; Freitas, Carlos Clayton Macêdo de [UNESP]; Luvizutto, Gustavo José; Lima Sobreira, Marcone; Escobar Bueno Peixoto, Daniel; Do Nascimento MagalhÃes, Inaldo; Bazan, Rodrigo; Pereira Braga, Gabriel (Karger Publishers, 2014)
Takayasu's arteritis is a chronic inflammatory disease, and neurological symptoms occur in 50% of cases, most commonly including headache, dizziness, visual disturbances, convulsive crisis, transient ischemic attack, stroke and posterior reversible encephalopathy syndrome. The aim of this study was to report the case of a young Brazilian female with a focal neurological deficit. She presented with asymmetry of brachial and radial pulses, aphasia, dysarthria and right hemiplegia. Stroke was investigated extensively in this young patient. Only nonspecific inflammatory markers such as velocity of hemosedimentation and C-reactive protein were elevated. During hospitalization, clinical treatment was performed with pulse therapy showing improvement in neurological recuperation on subsequent days. In the chronic phase, the patient was submitted to medicated angioplasty of the brachiocephalic trunk with paclitaxel, with significant improvement of the stenosis. At the 6-month follow-up, the neurological exam presented mild dysarthria, faciobrachial predominant disproportionate hemiparesis, an NIHSS score of 4 and a modified Rankin Scale score of 3 (moderate incapacity). In conclusion, Takayasu's arteritis must be recognized as a potential cause of ischemic stroke in young females.